2019
DOI: 10.1371/journal.pone.0214321
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant CD45RC expression on blood T cells differentiates patients with cancer and rejection after kidney transplantation

Abstract: Background Biological biomarkers to stratify cancer risk before kidney transplantation are lacking. Several data support that tumor development and growth is associated with a tolerant immune profile. T cells expressing low levels of CD45RC preferentially secrete regulatory cytokines and contain regulatory T cell subset. In contrast, T cells expressing high levels of CD45RC have been shown to secrete proinflammatory cytokines, to drive alloreactivity and to predict acute rejection (AR) in kidney t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…CD45RC is an isoform of CD45 that we showed to be expressed at least in both rats [3][4][5][6][7][8][9][10] and humans [11][12][13][14] at high levels in T cells (T CD45RC high ) precursors of Th1 as well as in terminally differentiated effector memory (TEMRA) cells that are responsible for acute solid organ rejection and aGVHD. Conversely, Th2 precursors as well as CD4 1 and CD8 1 Foxp3 1 Treg that are able to inhibit acute solid organ rejection and aGVHD are all CD45RC low/both in rats [3][4][5][6][7][8][9][10] and humans.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…CD45RC is an isoform of CD45 that we showed to be expressed at least in both rats [3][4][5][6][7][8][9][10] and humans [11][12][13][14] at high levels in T cells (T CD45RC high ) precursors of Th1 as well as in terminally differentiated effector memory (TEMRA) cells that are responsible for acute solid organ rejection and aGVHD. Conversely, Th2 precursors as well as CD4 1 and CD8 1 Foxp3 1 Treg that are able to inhibit acute solid organ rejection and aGVHD are all CD45RC low/both in rats [3][4][5][6][7][8][9][10] and humans.…”
Section: Introductionmentioning
confidence: 81%
“…Conversely, Th2 precursors as well as CD4 1 and CD8 1 Foxp3 1 Treg that are able to inhibit acute solid organ rejection and aGVHD are all CD45RC low/both in rats [3][4][5][6][7][8][9][10] and humans. [11][12][13][14] In a solid organ transplantation fully MHC-incompatible rat model, we showed that a short course of anti-CD45RC mAb treatment induced preferential depletion of CD45RC high T cells leading to permanent allogeneic tolerance through the induction of activated donor-specific CD8 1 and CD4 1 Tregs. 9 In anti-CD45RC-treated animals, memory and de novo immune responses were preserved.…”
Section: Introductionmentioning
confidence: 99%
“…In their study from 2019, Garnier et al[ 85 ] examined the pretransplant populations of cluster of differentiation forty five isoform with alternative mRNA splicing of exon (CD45RC) T cells in 89 KTRs. CD45RC expression dictates either a more regulatory (low expression) phenotype or pro-inflammatory (high expression) phenotype.…”
Section: Novel Biomarker Classificationmentioning
confidence: 99%
“…CD45RC expression dictates either a more regulatory (low expression) phenotype or pro-inflammatory (high expression) phenotype. Intriguingly, they found that differences in these populations predicted opposing outcomes: KTRs with a low CD4+CD45RC high population (< 51.9%) carried a 3.7 fold risk of cancer [HR = 3.71 (95%CI: 1.24 to 11.1); P = 0.019] vs the high CD4+CD45 high population having a 20-fold higher risk of rejection [HR = 21.7 (95%CI: 2.67 to 176.2); P = 0.0004][ 85 ]. The results of these studies are illustrated in Table 10 .…”
Section: Novel Biomarker Classificationmentioning
confidence: 99%
“…We demonstrated in a previous work that the level of CD45RC expression at the surface of blood CD8 + T cells before kidney transplantation was associated with the risk of AR after transplantation [10,13]. This study was conducted on a cohort of 89 kidney transplant recipients transplanted between 1999 and 2004, and we observed that a pre-transplant proportion of CD8 + CD45RC high T cells above 54.7% conferred a 6-fold increased risk of developing AR after 4.8 years of follow-up [10].…”
Section: Introductionmentioning
confidence: 99%